Dose-adjusted EPOCH-R (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab) in untreated aggressive diffuse large B-cell lymphoma with MYC rearrangement: a prospective, multicentre, single-arm phase 2 study. Issue 12 (December 2018) - Dunleavy, Kieron; Fanale, Michelle A; Abramson, Jeremy S; Noy, Ariela; Caimi, Paolo Fabrizio; Pittaluga, Stefania; Parekh, Samir; Lacasce, Ann; Hayslip, John W; Jagadeesh, Deepa; Nagpal, Sunil; Lechowicz, Mary Jo; et al.
Summary: Background: MYC gene rearrangement is present in approximately 10% of aggressive B-cell lymphomas, with half also harbouring a BCL2 gene rearrangement. Multiple retrospective studies of R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone or prednisolone) have shown a worse outcome in patients with MYC rearrangement (alone or with rearrangement of BCL2 or BCL6, or both) than in patients without MYC rearrangement, and suggest improved outcomes after more intensive treatment. We aimed to determine the outcome of dose-adjusted EPOCH-R (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab; DA-EPOCH-R), an intensive infusional treatment regimen, in untreated aggressive B-cell lymphoma with MYC rearrangement. Methods: We present the final analysis of a prospective, multicentre, single-arm, phase 2 study of DA-EPOCH-R in patients with untreated aggressive B-cell lymphoma with MYC rearrangement. DA-EPOCH-R was scheduled to be administered with CNS prophylaxis for six cycles. Primary endpoints included event-free and overall survival. This study is registered withClinicalTrials.gov (NCT01092182 ). Findings: 53 patients were enrolled, with median age of 61 years (range 29–80; IQR 50–70); 43 (81%) patients had stage III–IV disease and 26 (49%) had high-intermediate or high international prognostic index (IPI) scores. 19 patients had confirmed MYC rearrangement alone (single-hit) and 24 also had rearrangement of BCL2, BCL6, or both (double-hit), with similar characteristics between these two groups. After a median follow-up of 55·6 months (IQR 50·5–61·1), 48-month event-free survival was 71·0% (95% CI 56·5–81·4) and 48-month overall survival was 76·7% (95% CI 62·6–86·1) for all patients. Toxicity included grade 4 neutropenia in 160 (53%) of 301 cycles, grade 4 thrombocytopenia in 40 (13%) cycles, and any grade of fever with neutropenia in 56 (19%) cycles. There were three treatment-related deaths (all infections). Interpretation: In this study, DA-EPOCH-R produced durable remission in patients with MYC -rearranged aggressive B-cell lymphomas and should be considered for the treatment of these diseases. Funding: Cancer Trials Support Unit and Center for Cancer Research of the National Cancer Institute and Genentech.